Warfarin should not be used for thromboprohylaxis in elective major orthopaedic surgery: a Croatian perspective - Robert Kolundžić; Marijana Šimić Jovičić; Maja Ðinkić; Tadija Petrović; Tomislav Crnković; Vladimir Trkulja (Medicinski glasnik, 2017)
Aim: To identify modes of venous thromboembolism (VTE) prophylaxis in patients undergoing elective major orthopaedic surgery (total hip or knee arthroplasty, THA/TKA) at a single university-associated hospital in Croatia. Methods: A retrospective analysis of consecutive patients subjected to THA or TKA over a two-year period (2014-2015) with a focus on anticoagulation during the first 15 post-surgical days (period of highest VTE risk). Results: Of 603 identified patients three (0.5%) were not anticoagulated (haemophilia) and others received perioperative doses of low molecular weight heparins (LMWH). Overall, 228 (37.8%) patients received prophylaxis not involving warfarin, and 372 continued with short-term LMWH with switching to warfarin. They contributed a total of 1218 international normalized ratio (INR) values (median=3, range=1-8). These were consistently below the target INR range across the observed period. Between post-surgical days 6 and 15 (after the initial titration), 438 values were taken in patients treated with LMWH+warfarin and 92.7% were below, and only 6.8% within the target range; 580 values were taken in patients already switched to warfarin, 74% were below and only 25% within the range. Conclusion: The prevailing mode of VTE prophylaxis was in a clear contrast to (then) actual professional guidelines, with inadequate monitoring and poor anticoagulation. There is no reason to expect a substantially different situation at other institutions across the country. The prevailing practice of VTE prophylaxis in major orthopaedic surgery in Croatia should be promptly abandoned and updated in agreement with the current state of the art.
Keywords: hip; knee; arthroplasty; venous thromboembolism